PROBLEMS AND APPROACHES IN CHILDREN FIRST LANGUAGE ACQUISITION AT AGE 1-3 YEARS OLD IN YEMEN - Ali Mohammed Saleh Al-Hamzi; Ni Wayan Sartini; Abdul Hakim Ahmed Sallam Al-Shrgabi; Jamal Nasser Saleh Al-Maamari (Prasasti: Journal of Linguistics)
This study argues the problems and approaches in acquiring the first language at age 1-3 years by children in Yemen. Some stages like pre-production, early production, stage of the first-word stage, beginning fluency in its beginning intermediate, and advanced level are treated in this study. To solve the problem, theories relating to acquiring the first language are employed, these theories include (Varshney, 2003), (Lyons, 1981), (Bolinger, 2002), (Chomsky, 2009), (Gleason J. B., 1998), (Steinberg D. D., 2003), (Fromkin, 1983), (Langacker, 1973), (Wells, Children’s Language and Learning, 1980). This study is carried out by employing descriptive qualitative research. The target children are from Yemen aged 1-3 years old. The researcher’s daughter and son are taken as a subject for this study. Then he observed them for a long time and recorded them by using video aids that help him to collect data. After collecting the data, the researcher notices some problems regarding acquiring the first language. These problems include errors in speech sounds, incorrect words, reproduction, duplication, rectification, specifying the question, naming by experience, single-word response. He also finds out a number of approaches regarding acquiring the first language like pre-production, early production, first word, beginning fluency stage, intermediate fluency stage, and advanced fluency stage. Finally, Children first language acquisition can be arisen by exposing it to their parents and others surrounding them.